Vitamin and mineral supplementation for β-thalassemia during COVID-19 pandemic - Annette d'Arqom; Melvanda G Putri; Yovani Savitri; Andi Muh Rahul Alfaidin (Future Science OA)
Aim: Low levels of immune-related micronutrients have been identified in β-thalassemia samples. Moreover, the excess amount of iron, contributing to oxidative stress in the pathogenesis of the disease, alters the immune system in β-thalassemia, which is important during the COVID-19 pandemic. Materials & Methods: Searches of PUBMED and EMBASE were conducted to identify the level and supplementation of micronutrients in β-thalassemia, published from 2001–May 2020. Results: The review found six observational and five interventional studies supporting the importance of supplementing vitamins and minerals among patients with β-thalassemia. Conclusion: Supplementation of immune-related vitamins and minerals might bring benefits to the immune system, especially in reducing oxidative stress in β-thalassemia.